ChemInform Abstract: Chiral Boron Complex‐Promoted Asymmetric Diels—Alder Cycloaddition and Its Application in Natural Product Synthesis. Issue 23 (May 2016) - Li, Xia; Han, Jianguang; Jones, Alexander X.; Lei, Xiaoguang
Abstract: A preformed chiral boron‐complex including a VANOL‐type ligand is efficiently employed as catalyst for the enantioselective Diels—Alder reaction of 2‐hydroxychalcones [cf.